A Preliminary Evaluation of Adapted Cognitive Behavior Therapy for Anxiety in Adolescents with Mild Intellectual Disability in Indonesia - Harahap, Dinda Permatasari; Harahap, Ade Chita Putri (Islamic Guidance and Counseling Journal, 2026)
Individuals with mild intellectual disability (MID) experience elevated rates of anxiety that adversely affect emotional well-being and social participation. Although Cognitive Behavioral Therapy (CBT) is well-established for anxiety in the general population, evidence for its use with individuals with MID remains limited. This case series explored the feasibility and preliminary clinical outcomes of an adapted CBT intervention for anxiety in adolescents with MID. Four adolescents (aged 14 years) with clinically significant anxiety received seven sessions of CBT adapted through simplified language, visual supports, repetition, role-play, and caregiver involvement. Anxiety was assessed at pre-intervention, post-intervention, and follow-up using the Glasgow Anxiety Scale for People with an Intellectual Disability (GAS-ID). Individual change was evaluated using the Reliable Change Index (RCI). Qualitative data from participant worksheets and supporter interviews were analyzed thematically. All participants demonstrated reliable reductions in anxiety symptoms that were maintained at follow-up. Qualitative findings suggested improvements in emotional awareness, social participation, and coping skills. These findings indicate that adapted CBT may be feasible and potentially beneficial for adolescents with MID, warranting further evaluation in controlled studies.